Semi-quantitative immunohistochemical detection of 5-hydroxymethyl-cytosine reveals conservation of its tissue distribution between amphibians and mammals - Almeida, Rimple D.; Sottile, Virginie; Loose, Matthew; De Sousa, Paul A.; Johnson, Andrew D.; Ruzov, Alexey (Landes Bioscience, 2012)
5-Hydroxymethyl-cytosine (5-hmC) is a form of modified cytosine, which has recently attracted a considerable attention due to its potential role in transcriptional regulation. According to several reports 5-hydroxymethyl-cytosine distribution is tissue-specific in mammals. Thus, 5-hmC is enriched in embryonic cell populations and in adult neuronal tissue. Here, we describe a novel method of semi-quantitative immunohistochemical detection of 5-hmC and utilize it to assess the levels of this modification in amphibian tissues. We show that, similar to mammalian embryos, 5-hmC is enriched in axolotl tadpoles compared with adult tissues. Our data demonstrate that 5-hmC distribution is tissue-specific in amphibians, and that strong 5-hmC enrichment in neuronal cells is conserved between amphibians and mammals. In addition, we identify 5-hmC-enriched cell populations that are distributed in amphibian skin and connective tissue in a mosaic manner. Our results illustrate that immunochemistry can be successfully used not only for spatial identification of cells enriched with 5-hmC, but also for the semi-quantitative assessment of the levels of this epigenetic modification in single cells of different tissues.